WOMEN EMPOWERMENT THROUGH MANAGEMENT OF ORGANIC AND ANORGANIC RUBBISH - Sujarwo, M.Pd., Sujarwo (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
The avtivitiy of management organic and anorganic rubbish for women in Hunian Tetap (Huntap)  Glagaharjo is one of the activities to build the society awareness about management of rubbish which have high value. The purpose of this activity are to provide knowledge and skills for women and improve the economi of women. This activity carried out by need assessment of society and abundance of trash from the eruption of merapi. Implementation of the activities carried out by andragogy approach to 25 women. The results shows that the activities of rubbish  managament have increased the motivation, knowledge, and skills of women in management of organic and anorganic rubbish into compost and accessories (bag, brooch,and plastic flower). Therefore, development of target group needs to be done in a sustainable manner and involving  the relevant stakeholders to create the environment which everlasting and productive